Inovação, novos conceitos ampliados: oportunidades para empresas - Morgado, Eduardo Martins [UNESP] (My University, 2011)
This article describes the evolution of Innovaton concepts, specifically Technological Innovation. It seeks to demonstrate that this conceptual evolution opens new paths for the development of Innovations and for the creation of Competitive Opportunities. It presents a model for searching and assessing the risk of these innovations regarding the adopted Technologies and the targeted market. A traditional tool for the Adoption of Innovations is introduced to be used in risk assessment. We seek to propose a strategy to search for, to identify and to assess innovations based on the involvement of the entire organization, by means of activities guided by creativity. Important aspects regarding the process of adopting Innovations are described to demonstrate the importance of the "time" dimension, as well as to contribute for the Innovation search practice.

Este artigo descreve a evolução dos conceitos da Inovação e Inovação tenológica permitindo às empresas oferecendo às empresas maiores alternativas na criação de oportunidades competitivas. Descreve também de forma geral, alternativas para a geração de Inovações, destacando a importância da aproximação com as principais fontes de Inovação, que no Brasil, são as Universidades e seus Centros de Pesquisa, através de programas incentivados pelo Ministério de Ciências e Tecnologia.
Keywords: Innovation; Technological innovation; New concepts of innovation; Innovation strategies; Inovação; Inovação tecnológica; Conceitos de inovação